Development of Health Promotion and Disease Prevention and Control Program by Using Strategic Route Map: In a Case of Hat Asa Subdistrict, Sapphaya,District Chainat Province - อังคศรีทองกุล, สุจิตรา; อึ้งพานิชย์, วราภรณ์ (Disease Control Journal, 2018)
The objective of participatory action research was to develop health promotion and disease prevention and control program by using Strategic Route Map (SRM) at Hat Asa subdistrict, Sapphaya district, Chainat Province. Total 9 communities of Hat Asa subdistrict were included into this study for three years from October 2007 to September 2009. The group process including Mind map, SRM, group relationship and knowledge management were used to design the disease prevention strategic and action plans of local health networks. The implementation was classified into 3 phases. The 1st phase, training the core groups of networks were trained to create a SRM and action plans of Hat Asa subdistrict. The 2nd phase, Second year, the local health networks were trained to use SRM for developing local health strategic and action plan at the sub-district level. The last phase, the community leaders were trained to build up an action plan in village level. The results revealed that 1. The strategic plan for 4 year periods (2550-2553) of Hat Asa local authority organization including the implementation plan was developed by the participation of all stake holders. The leaders of health network and local health trust fund committee were able to create the action plan by using the SRM. The manual and guideline for using SRM were developed and distributed to all target groups so that all communities were able to develop their own action plans for disease prevention and control and were supported the funding from the local health trust fund committee. Up to now, Hat Asa subdistrict was accepted to be a prototype area of development of disease prevention and control program, with participatory action of health network, by using SRM.